Depressive symptoms in Icelandic elite athletes: A prospective examination through the lens of the response styles theory. (September 2021) - Tahtinen, R.E.; Kristjánsdóttir, H.; þorgeirsson, S.; Oddson, H.R.; Saavedra, J.M.; Morris, R.
Abstract: The aim was to explore depressive symptoms through the response styles theory in Icelandic elite athletes using a longitudinal research design. A total of 79 Icelandic elite and national team athletes were included in the study (M = 23.5, SD = 4.8, age range 18–37, females 75.9%). Higher perceived stress and brooding rumination (maladaptive response to negative mood) independently predicted higher depressive symptom scores over the study period. Athletes who reported higher brooding tendencies in the beginning of the study, were significantly more likely than those reporting lower tendencies, to report higher increases in depressive symptoms when stress levels increased over the study period. The findings supported the validity of exploring individual differences in depressive symptoms through the lens of the response styles theory in the athletes. Future research could explore the relationship between brooding rumination, athletic performance, and mental health issues, and test interventions targeting brooding rumination in athletes. Highlights: Changes in perceived stress predicted changes in depressive symptom scores over time. Higher brooding rumination scores predicted higher depressive symptom scores over time. Higher reflective rumination scores did not predict higher depressive symptom scores over time. Brooding rumination moderated the prospective relationship between perceived stress and depressive symptoms.